Causes and preventive measures of needlestick injury among grass-roots nurses in centralized vaccination sites (疫苗集中接种点基层护士针刺伤原因及防范措施) - ZHANG Ying (张莹); WANG Li (王丽); TIAN Shiyuan (田士源) (中西医结合护理)
There are many hidden dangers if needlestick injuries occurs among grass-roots nurses at COVID-19 vaccination sites. In order to better prevent the occurrence of needlestick injuries and blood-borne infectious diseases, the related causes and relevant prevention and control measures were reviewed in this study. (本文就新型冠状病毒疫苗集中接种点针刺伤发生的相关原因和预防措施进行综述, 旨在更好地预防针刺伤及血源性传染病的发生。)